Culturally adapted mobile application for optimizing metabolic control in type 1 diabetes: a pilot study - Cepeda-Marte, Jenny L.; Moore, Arelis; Ruiz-Matuk, Carlos B.; Salado-Díaz, Daniela D.; Socias-Pappaterra, Pablo; Ho-Sang, Vivian W.Y.; Mella-Bonilla, Isabella (Revista panamericana de salud pública, 2024)
Objective. To evaluate whether use of a culturally adapted mobile application (app) for adolescents with type 1 diabetes is associated with improved metabolic control. Methods. The Dominican Republic’s National Institute of Diabetes, Endocrinology, and Nutrition and the Learning to Live clinic recruited 23 pediatric participants for the study. Blood tests were performed before and after use of the app for a period of 3 months. Based on the user profile, participants were encouraged to use the app’s bolus insulin calculator after each meal. The app included a list of regionally and culturally specific foods, color-coded to indicate a high glycemic index (GI) as red; medium GI as yellow; and low GI as green. The color-coding was designed to assist participants in making healthier eating choices. Results. There were statistically significant improvements in lipid profile. Mean high-density lipoprotein values rose to acceptable levels, while low-density lipoproteins and triglyceride levels fell to the recommended values. The overall quality of life increased, although glycated hemoglobin levels showed no statistically significant changes. Conclusion. The findings of this study suggest that using this culturally tailored app can help young patients with type 1 diabetes to improve metabolic health.